PENENTUAN SEKTOR UNGGULAN DI KABUPATEN ALOR TAHUN 2017-2021 - Sogara, Mateus Umbu; Adar, Damianus; Siubelan, Yacobus C.W. (Undana Press, 2024)
This research aims to determine the leading sectors in Alor Regency so that the local government focuses on developing its region by using secondary data published by the Alor Regency Central Statistics Agency (BPS) for the 2017-2021 period which covers 17 business sectors based on constant prices. The Location Quotient (LQ) and Dynamic Location Quotient (DLQ) approaches were used to analyze the superior sectors of Alor Regency to obtain conclusions, sectors (1) agriculture, forestry and fisheries sectors; (2) mining and quarrying sector; (3) processing industry sector; (4) electricity and gas procurement sector; (5) waste, waste and recycling processing water supply sector; (6) wholesale and retail trade sector, car and motorbike repairs; (7) transportation and warehousing sector; (8) financial services and insurance sector; (9) corporate services sector; and (10) the government administration, defense and social security sectors are mandatory economic base sectors which are expected to remain the economic base in the future. Meanwhile, judging from the shift share approach, there are 7 (seven) sectors that have competitive advantages or have high competitiveness in Alor Regency, including: (1) Agriculture, Forestry, Fisheries sectors; (2) Electricity and Gas Procurement sector; (3) Water Supply, Waste Processing, Waste and Recycling sectors; (4) Construction sector; (5) Information and Communication sector; (6) Financial Services and Insurance sector; and (7) the Health Services and Social Activities sector.